Design, Synthesis and Anti-Breast Cancer Activity of New Benzimidazole-1,2,4-thiadiazoles-benzamide Hybrids - Sheelam, Saritha; Mandala, Jyothi (Asian Journal of Chemistry, 2026)
A new series of benzimidazole-1,2,4-thiadiazole-benzamide hybrids (7a-l) was synthesized and characterized. The synthesized hybrids were evaluated for anticancer activity against two breast cancer cell lines, MCF-7 and MDA-MB-231, using the MTT assay, with Erlotinib as the reference drug. The results revealed that hybrid 7i exhibited more potent activity against both tested cancer cell lines than the standard drug Erlotinib. The other three hybrids, 7j, 7k and 7l, displayed activity values close to that of the standard drug. Based on these findings, hybrids 7i, 7j, 7k and 7l were further evaluated for tyrosine kinase EGFR inhibitory activity using Erlotinib as the reference drug. Hybrids 7i and 7j exhibited higher EGFR inhibitory activity than erlotinib. Molecular docking studies of the potent hybrids with the EGFR receptor supported the biological results, with hybrids 7i and 7l exhibiting strong interactions with the EGFR protein and superior binding affinities compared with erlotinib. The combined anticancer, EGFR inhibitory and docking results identify hybrid 7i as the most promising hybrid, while hybrids 7j and 7l represent potential EGFR-targeting anticancer candidates.